Tradisi Hagiografi Sufi YasawÃ®: Relasi Tasawuf dan Politik - Asmawi, Asmawi (ISLAMICA: Jurnal Studi Keislaman, 2006)
Every method and approach in Islamic Studies currently available to us hasweaknesses in looking at religious data. For that reason, efforts to find better and moreintegrative method are needed. One of the approaches that might be useful for IslamicStudies is historical approach. Sufism in the meantime, has become an important partof the history of Islam. Nonetheless, it is only recently that Sufismâas well as its origin,change and development- become a subject of historical study. Hagiography has alsobecome a new trend in the historical study of Sufism. And one of the Sufis whosehagiography has become an important subject of study is that of Ahmad Yasafi, a Sufi of16th â 17th century. Hagiography is a kind of written sources that narrate the life of asupposedly holy man and the legends related to him. According to Devin Dewees, thehagiography of Ahmad Yasawi portrays the manâs personal and communal life, hispatronage with the ruler, the rituals of his tarÃ®qah, and the legends related to him and hisorder. This article âusing historical approach- is a descriptive account of Ahmad Yasawiâshagiography.